2022
DOI: 10.5935/1984-0063.20200130
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chronotype on the body mass index of U.S. college students

Abstract: Objectives The relationship between a college student’s chronotype and body mass index (BMI) is important to understand for university decision makers who want to build healthy and inclusive academic communities. This study aimed to evaluate how a student’s chronotype influences their BMI. Material and Methods Participants were college students from Oral Roberts University (n=384) with a mean age of 18.94 years, a mean BMI of 24.7kg/m 2 , and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Finally, as this was a cross-sectional study conducted at three universities with a limited number of participants, future research should examine changes in body composition in relation to changes in chronotypes and lifestyle behaviors. Although the sample size in this study was similar to that in recent studies on the association between chronotype and body composition in university students [ 7 , 9 , 11 ], further research is required to investigate this association at more universities with a larger number of participants.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Finally, as this was a cross-sectional study conducted at three universities with a limited number of participants, future research should examine changes in body composition in relation to changes in chronotypes and lifestyle behaviors. Although the sample size in this study was similar to that in recent studies on the association between chronotype and body composition in university students [ 7 , 9 , 11 ], further research is required to investigate this association at more universities with a larger number of participants.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have suggested that the association between BMI and chronotype may vary based on factors such as location, age, and gender [ 9 ], as well as among different racial/ethnic groups [ 7 ]. However, our study with Japanese female students found that body composition was related to chronotype and physical activity, similar to a previous study with German students (which did not investigate nutrient intakes) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results may be related to age, in particular, the leveling of the role of reproductive hormones, which are closely related to the evening type in young men and the morning type in pre-menopausal women [35; 36]. It was also found that BMI increases significantly with age and with index of composite scale of morningness, evening chronotypes gaining weight faster than morning chronotypes [37].…”
Section: Resultsmentioning
confidence: 98%
“…However, these studies found conflicting results. Studies spanning adolescents to older adults found that evening chronotypes had greater body mass indexes (BMI; kg•m −2 ) (Arora & Taheri, 2015;Bloom et al, 2022;Teixeira et al, 2022), while other studies in similar age groups found no relationship between chronotype and BMI, waist circumference, or body fat (Kandeger et al, 2018(Kandeger et al, , 2019Lai & Say, 2013;Mota et al, 2016;Sato-Mito et al, 2011;Teixeira et al, 2018).…”
Section: Introductionmentioning
confidence: 97%